The Interaction between In-Cylinder Turbulent Flow and Flame Front Propagation in an Optical SI Engine Measured by High-Speed PIV - Yuji Ikeda (Energies, 2022)
The relationship between the flow field and flame propagation is essential in determining the dynamics and effects of turbulent flow in an optical SI engine. In this study, high turbulence flow at stable operations was achieved using 12,000 rpm engine speed, 60 kPa absolute intake pressure, 14.7 A/F, and 15 deg. BTDC spark timing. The turbulent flow field and flame propagation interplay were analyzed through the simultaneous high-speed PIV measurements of the in-cylinder flow and flame front propagation under firing conditions. The intensity of the seeder used was optimized by changing the crank angle. Successful simultaneous detection of the flame front and turbulent flow was demonstrated. Strong turbulence was produced at the flame front simultaneously with the flame movement. After ignition timing, the flame accelerated in the unburned region, and a vital turbulence region occurred.